Исследование физических процессов, протекающих при генерации ударной звуковой волны в газогенераторных станциях - Хачатрян, A. Ж.; Агабекян, В. Н.; Акопян, А. С.; Мосоян, Д. О. (Հայաստանի ԳԱԱ)
A study was made of the physical processes occurring during the generation of a shock wave carried out at the outlet of a nozzle of a gas-generator station, when emitted into the atmosphere, at a supersonic velocity of the gas mixture formed in the chamber during gas combustion. Investigations of the spectral characteristics of an excited shock sound wave was made as well as the corresponding calculations of its height of wave propagation dependences were carried out. The dependences of the intensities of obtained sound waves on the frequency were calculated. The intensity levels of the action of sound waves on the clouds were determined depending on the height of their location. The obtained values of the surface energy densities of the excited sound waves at heights of 500 m, 750 m and 1000 m are 0.258 J/m2, 0.115 J/m2, 0.064 J/m2 respectively. In results, effects of these waves on hail clouds can be noticeable only at altitudes of the order of 500 m.
Keywords: Geophysics